On the Variational Problems without Having Desired Variational Symmetries - Mehdi Nadjafikhah; Saeed Dodangeh; Parastoo Kabi-Nejad (Journal of Mathematics)
We will have an attempt to present a method for constructing variational problems without having a desired one-parameter transformation group as a variational symmetry. For this, we use the notation of μ-symmetry which was introduced by Giuseppe Gaeta and Paola Morando in 2004. Moreover, our given method enabled us to solve those constructed variational problems using μ-symmetries.